2021
DOI: 10.1021/acsami.1c18978
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Exchange Strategy to Achieve Chiral Perovskite Nanocrystals with a High Photoluminescence Quantum Yield and Regulation of the Chiroptical Property

Abstract: Chiral nanomaterials have drawn extensive attention on account of numerous application prospects in optoelectronics, asymmetric catalysis, chiral recognition, and three-dimensional (3D) display. Thereinto, chiral perovskite has been a hotspot due to brilliant optoelectronic properties, but some problems limit the development, including low quantum yield, low chiral intensity, and the lack of facile regulation. To overcome these issues, an effective ligand exchange strategy, i.e. the interface modification has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 70 publications
1
38
0
Order By: Relevance
“…313 In addition, several attempts were made in inducing the chirality in bulklike LHP nanocubes using chiral ligands. 237,310,316 In this regard, Kim et al 310 proposed both ligand-controlled synthesis and postsynthetic ligand exchange to obtain chiral FAPbBr 3 NCs using the short chiral ligands (R)-2-octylamine and (S)/(R)-MBA-Br. The anchoring of (R)-2-octylamine to FAPbBr 3 NCs results in chiral perovskite NCs that emit CPL with a relatively high luminescence dissymmetry (g lum ) factor of 6.8 × 10 −2 .…”
Section: Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…313 In addition, several attempts were made in inducing the chirality in bulklike LHP nanocubes using chiral ligands. 237,310,316 In this regard, Kim et al 310 proposed both ligand-controlled synthesis and postsynthetic ligand exchange to obtain chiral FAPbBr 3 NCs using the short chiral ligands (R)-2-octylamine and (S)/(R)-MBA-Br. The anchoring of (R)-2-octylamine to FAPbBr 3 NCs results in chiral perovskite NCs that emit CPL with a relatively high luminescence dissymmetry (g lum ) factor of 6.8 × 10 −2 .…”
Section: Transformationsmentioning
confidence: 99%
“…For instance, Ye et al found that the replacement of a short–long-chain with long-chain acid–base pair (OAm and OA) drastically improves the colloidal stability and the device performance of the corresponding LEDs. Besides, various other exchanging ligands, including thiols; ,,, thionyl halides; phosphonic acids; ,, phenethylammonium (PEA + ); cinnamate acid; chiral molecules; and zwitterionic molecules (including bi- and multidentate ligands), such as iminodibenzoic acid, ethylenediaminetetraacetic acid (EDTA)–glutathione (GSH), , trithiocarbonate (TTC), heterocyclic aromatic carboxylates, and zwitterionic polymers, ,, have been potentially exploited to replace native ligands of LHP NCs. In addition, neutral ligands, such as carboxylic acid, sulfonic acid, and phosphonic acids, can replace the alkylammonium cations, as well as etch the surface, of LHP NCs .…”
Section: Ligand Exchangementioning
confidence: 99%
“…39 In order to improve the chiro-optical properties of perovskite nanomaterials, researchers have explored the importance of structural aspects, such as using mixed ligand shells, 36 manipulating the perovskite lattice-spacing ( d -spacing) and halogen–halogen interaction, 40 and changing the concentration of chiral ligand during post-synthetic ligand exchange. 38 While structural distortions can provide a straightforward mechanism for symmetry breaking, it does not necessarily translate into the significant “electronic” chirality that is probed by CD and CPL spectroscopy. Thus, one must also consider how the electronic interactions between chiral ligands and the NP contribute to the chiro-optical response.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to look carefully not only at the nature of the functional group present on the molecule and its isolated interaction strength with the NC surface defects, but also at its position on the molecule and the steric hindrance for the interaction with the NC. Other functionalized molecules can also be explored to be used during the ligand exchange step, including chiral ligands, 234 methoxy silane-based molecules, 235 potassium bromide, 236 zinc methacrylate (ZnMA), trioctylphosphine oxide (TOPO) co-passivation, 237 and zwitterions, as sulfobetaine and phosphocholine.…”
Section: Pnc Solar Cellsmentioning
confidence: 99%